Graphene oxide incorporated novel polyvinyl alcohol composite membrane for pervaporative recovery of acetic acid from vinegar wastewater. (December 2016) - Dave, Haresh K.; Nath, Kaushik
Highlights: GO and PVA nanocomposite for pervaporation of vinegar wastewater. Enhanced mechanical strength and thermal stability of the composite. Overall decrease in relative crystallinity compared to the pristine membrane. An improved hydrophilicity and pervaporation flux of the membrane. Higher permeability and diffusivity of water. Abstract: A novel polymeric composite membrane consisting of graphene oxide (GO) and poly (vinyl alcohol) (PVA) has been developed and applied in the recovery of acetic acid from vinegar wastewater in a pervaporation unit. The resultant composite membranes designated as (PVA-GO)1 and (PVA-GO)2 were characterized by using X-ray diffractions, scanning electron microscopy, Fourier-transform infrared spectroscopy, atomic force microscopy and thermogravimetric analysis. Membranes were found to attain semi-crystalline to amorphous nature by incorporation of GO to PVA. GO incorporation in the PVA membrane was observed to have a profound influence, as it helped achieve better thermal stability and higher tensile stress compared to pristine PVA membrane. The composite membranes were prone to swelling in presence of water. GO imparted better hydrophilicity of the composite membranes as displayed by a reasonably high degree of volumetric flux of water and separation factor. The study demonstrates that GO can be effectively incorporated within the polymer matrix to tune the mechanical and permeation characteristics of nanocomposites.